Effects of different smoking methods on sensory properties, free amino acids and volatile compounds in bacon. (20th November 2020) - Guo, Jie; Wang, Qiong; Chen, Conggui; Yu, Hai; Xu, Baocai
Abstract: BACKGROUND: The aim of this study was to investigate the effects of different smoking methods on sensory properties, free amino acids (FAAs) and volatile compounds (VCs) of bacon. Descriptive analysis was performed using a highly trained panel ( n = 9) to evaluate four bacons in sextuplicate. VCs of bacons were analyzed using solid‐phase microextraction (SPME) coupled with gas chromatography–mass spectrometry (GC–MS). RESULTS: Bacons were significantly different in sensory properties ( P  < 0.05). Wood smoked bacon (WSB) had a higher smoky and fatty aroma, liquid smoked bacon (LSB) had a higher red color intensity and yellow color intensity, and paper smoked bacon (PSB) had an outstanding texture. Different smoking methods resulted in an increase in total FAAs content, of which paper smoking was significantly higher than the others ( P < 0.05). Also, a total of 59 volatile flavor compounds were identified for bacons, aldehydes were the most abundant groups of compounds. Principal component analysis (PCA) can effectively separate the bacons that underwent different smoking methods. CONCLUSION: The aldehydes and hydrocarbons with high content in PSB improved the overall taste intensity. The color in the sensory attributes was more obvious after LSB processing. The phenols and aromatic hydrocarbons in WSB contributed significantly to the pleasant properties (smoky, fatty). © 2020 Society of Chemical Industry